Implementasi Metodologi Rekayasa Nilai Pendekatan Dell L. Younker pada Pengembangan Desain Penggiling Daging Manual bagi UMKM Pasar - Maulana, Rifky; Simbolon, Sardiana Sepriana; Sunggu, Rachuel Ar. Op; Mukaarim, Muhammad Naufal; Renata, Viana Tasya; Yanti, Assifa Serli; Wahyudi, Rizqi (CV Insan Kreasi Media, 2025)
A manual meat grinder is one of the essential tools for Micro, Small, and Medium Enterprises (MSMEs) in supporting the production process of meat-based food products. However, most of the designs available on the market still have several limitations, such as non-ergonomic working positions, low energy efficiency, and relatively high production costs. These conditions affect user productivity and comfort during operation. Based on these issues, this study aims to develop a more effective and valuable manual meat grinder design by applying the Value Engineering (VE) methodology based on Del L. Younker’s approach. The VE methodology is used to identify the main and supporting functions of the tool, analyze the relationship between cost and benefit, and generate alternative designs that can enhance functionality without compromising performance quality. The research process is carried out through six main stages: information, function analysis, creative, evaluation, development, and presentation. The results of the implementation show that the new design improves energy efficiency, reduces production costs, and enhances user comfort through ergonomic improvements. Thus, the Value in a single paragraph around 250-300 words. Engineering approach proposed by Del L. Younker has proven effective in supporting the development of simple, functional, and economical product designs that meet the needs of MSMEs.